O conselho disciplinar da penitenciária estadual de Francisco Beltrão - Pr: a educação dos apenados via disciplina institucional - Tozetti, Rodrigo Luiz (2021)
The purpose of the dissertation was to analyze the way in which the prisoner is “produced” in the state penitentiary in the city of Francisco Beltrão, Paraná, about the disciplinary rules consolidated within this institution. Norms that aim to educate the behavior of the inmates, inside such institution. Based on an attempt to contribute to the debate about the prison system and its practices, we seek - based on the writings and domains of the philosopher Michael Foucault, - to understand the historical trajectory of custodial sentences - their disciplinary contours -, to between the lines in this microcosm that is the prison. Thus, we seek to present the power / knowledge relations generated in the local prison environment. To this end, a bibliographic review of the research problem was added, addressing the historical, social, and regulatory aspects of the Brazilian and Paraná prison system. We present the survey on the Laws that regulate the “Disciplinary Council” provision in Francisco Beltrão's penitentiary, as well as the documents that regulate administrative procedures, which they judge as disciplinary transgressions committed by the inmates, while serving their sentences. This work took place from the relationship, which we seek to carry out, between this disciplinary entity and its educational work. In this perspective, the research conducted through research of the prison space located in the city of Francisco Beltrão - composing a case study -, which was carried out by conducting on-site research, carried out through review, and which took into consideration document analysis - Penal Execution Law 7210/84, Paraná Penitentiary Statute 1276/95, internal documents - and disciplinary procedures related to disciplinary faults committed by prisoners in the Francisco Beltrão prison system. The focal group technique was applied, with members of the Disciplinary Council of the penitentiary, in addition to interviews with the members who made up the direction of this institution. Through the data collected and the analyzes carried out, the research presented as a result the relationship between education and discipline, existing in PEFB, through practices influenced by that one. In this way, we seek to scrutinize the constitution of a field of knowledge (produced in the Disciplinary Council), and of the power relations arising therefrom. Towards the behavioral education of prisoners. The visible and invisible dimensions that the disciplinary device presents in the PEFB were problematized, related to organized crime, to the issue of overcrowding, related to access to formal education and or to work - by the inmates. Process that is endorsed by the Disciplinary Council. We tried to demonstrate, in this way, how the prisoner has been educated, in the PEFB, institutional discipline directed to him, during his sentence.